The emergence of resistance to the antiparasitic selamectin in Mycobacterium smegmatis is improbable and contingent on cell wall integrity - José Manuel Ezquerra-Aznárez; Henrich Gašparovič; Álvaro Chiner-Oms; Ainhoa Lucía; Jesús Blázquez; Iñaki Comas; Jana Korduláková; José A. Aínsa; Santiago Ramón-García (Microbiology Spectrum)
ABSTRACT Tuberculosis remains the deadliest infectious disease of the 21st century. New antimicrobials are needed to improve treatment outcomes and enable therapy shortening. Drug repurposing is an alternative to the traditional drug discovery process. The avermectins are a family of macrocyclic lactones with anthelmintic activity active against Mycobacterium tuberculosis. However, their mode of action in mycobacteria remains unknown. In this study, we employed traditional mutant isolation approaches using Mycobacterium smegmatis, a non-pathogenic M. tuberculosis surrogate. We were only able to isolate mutants with decreased susceptibility to selamectin using the ∆nucS mutator M. smegmatis strain. This phenotype was caused by mutations in mps1 and mmpL11. Two of these mutants were used for a second experiment in which high-level selamectin-resistant mutants were isolated; however, specific mutations driving the phenotypic change to high-level resistance could not be identified. The susceptibility to selamectin in these mutants was restored to the basal level by subinhibitory concentrations of ethambutol. The selection of ethambutol resistance in a high-level selamectin-resistant mutant also resulted in multiple colonies becoming susceptible to selamectin again. These colonies carried mutations in embB, suggesting that the integrity of the cell envelope is a prerequisite for selamectin resistance. The absence of increased susceptibility to selamectin in an embB deletion strain demonstrated that the target of selamectin is not cytosolic. Our data show that the concurrence of specific multiple mutations and complete integrity of the mycobacterial envelope are necessary for selamectin resistance. Our studies provide first-time insights into the antimycobacterial mode of action of the antiparasitic avermectins.IMPORTANCETuberculosis is the deadliest infectious disease of the 21st century. New antibiotics are needed to improve treatment. However, developing new drugs is costly and lengthy. Drug repurposing is an alternative to the traditional drug discovery process. The avermectins are a family of drugs used to treat parasitic infections that are active against Mycobacterium tuberculosis, the bacterium that causes tuberculosis. However, their mode of action in mycobacteria remains unknown. Understanding how avermectins kill mycobacteria can facilitate its development as an anti-mycobacterial drug, including against M. tuberculosis.In this study, we used Mycobacterium smegmatis, a non-pathogenic M. tuberculosis surrogate model to understand the molecular mechanisms of how selamectin (a drug of the avermectin family selected for this study as a model) acts against mycobacteria. Our data show that the generation of resistance to selamectin is unlikely and that complete integrity of the mycobacterial envelope is necessary for selamectin resistance, providing first-time insights into the antimycobacterial mode of action of the avermectins.